1996 service awards - De La Salle University, Manila (Animo Repository, 1996)
Thirty-three faculty members from different colleges received the 1996 Service Awards for those who have rendered valuable service to DLSU for many years while 28 others were awarded the 1996 Faculty Medal for those who have gained permanent tenure and who have been promoted in rank in the Annual Faculty Recognition Ceremony.